Development of Kinect based robot control system with obstacle avoidance capability - Chew, Boon Jin (2016)
Obstacle avoidance has been a developing field of research in robotics for many years. Different sensors were used in the past to obtain information on the obstacles. In this project, obstacle information obtained using Microsoft Kinect sensor was used to design a robotic control system capable of avoiding them. The control system is tested on a Selective Compliance Assembly Robot Arm (SCARA) industrial robot.